2020
DOI: 10.1007/s10648-020-09561-x
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Connections: A Framework to Guide Instructional Design for Developing Understanding in Complex Domains

Abstract: Research suggests that expert understanding is characterized by coherent mental representations featuring a high level of connectedness. This paper advances the idea that educators can facilitate this level of understanding in students through the practicing connections framework: a practical framework to guide instructional design for developing deep understanding and transferable knowledge in complex academic domains. We start by reviewing what we know from learning sciences about the nature and development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 102 publications
0
31
0
1
Order By: Relevance
“…Research in the learning sciences has demonstrated that flexible transfer is best supported when knowledge is coherent (for a review, see Fries et al 2020). If the goal of learning and teaching is to create coherent knowledge structures in novices, then students should not spend their time accruing bits of disconnected information (Let's learn about the median!…”
Section: Practicing Connections: the Whatmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in the learning sciences has demonstrated that flexible transfer is best supported when knowledge is coherent (for a review, see Fries et al 2020). If the goal of learning and teaching is to create coherent knowledge structures in novices, then students should not spend their time accruing bits of disconnected information (Let's learn about the median!…”
Section: Practicing Connections: the Whatmentioning
confidence: 99%
“…In this article, we describe the project that has resulted from our efforts. We base our approach on a clear theory of pedagogy, adapted from current thinking in the learning sciences, that we call the practicing connections framework (Fries et al 2020;Son, Ramos et al 2018). The practicing connections framework posits that to produce coherent transferable learning, students must practice making connections between core concepts, representations, and the world (i.e., contexts and practices involved in applying those concepts; cf.…”
mentioning
confidence: 99%
“…Dadurch werden sie anschlussfähiger an Diskurse in Wissenschaft und Praxis und können zu einer Weiterentwicklung der theoretischen Überlegungen führen (vgl. Fries et al 2020).…”
Section: Die Verknüpfung Von Unterrichtsdimensionen Und Lernprozessenunclassified
“…Decades of research have shown that when students are given opportunities to make connections between topics and ideas as they learn, they gain deeper understandings and are better able to transfer this knowledge to novel situations (Boaler, 2002, 2015; Boaler & Staples, 2008; Fries et al, 2021). Unfortunately, mathematics is often taught as a series of disconnected facts to be memorized and reproduced, which often leads students to opt out of mathematics courses once they are no longer required.…”
Section: Expanding Interest In Mathematicsmentioning
confidence: 99%